Efisiensi Tugas Dosen dalam Struktur Organisasi FMIPA Universitas Negeri Malang - Muh. Huda A.Y. (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
The problem studied is the working efficiency of lecturers within the organizational structure of the Faculty of Mathematics and Science (FMIPA), State University of Malang (UM). The design used is a survey involving the lecturers of the faculty. Data were collected using questionnaires, interviews, and inventory, and then analyzed statistically by t-test. The results show that among all the departments, student-lecturer ratio in the Department of Physics is efficient, while the ratio in the Mathematics, Chemistry, and Biology is inefficient. Viewed overall, student-lecturer ratio in FMIPA UM is inefficient. Among all the departments, lecturers' load in the Departments of Physics and Biology is efficient. From the point of view of lecturers' load, the work of lecturers in FMIPA UM is inefficient.